Pengembangan Sistem Pendeteksi Gangguan Spektrum Autisme dengan Menggunakan Metode Certainty Factor - Wulandari, Ika Arthalia; Siregar, Gunayanti Kemalasari (Universitas Muhammadiyah Magelang, 2024)
Autism Syndrome Disorder is a multifaceted developmental disorder of mental function with symptoms of impaired communication, social interaction, and distinctive behavioural patterns. A person with Autism Syndrome Disorder cannot form normal social relationships or communication. They have their world. This condition causes them to be isolated from the surrounding environment. Because the main problem faced in Indonesia is the misdiagnosis of autistic children as mentally retarded, so they cannot get the necessary treatment that allows these children to live like normal children. The diagnosis of autism is considered a big problem because the symptoms are easily confused with those of mental retardation. Diagnosis is one of the most challenging and complex problems due to the lack of specialist doctors who can diagnose it scientifically, resulting in misdiagnosis or neglect of autism in the early stages of a child's life, which leads to difficulties in intervention later in life. Successful intervention requires a correct diagnosis. Diagnosing autism disorders manually requires a specialist doctor, making this system have many shortcomings and weaknesses. Therefore, applying an expert system can help diagnose autistic disorders in patients. This expert system will be able to diagnose and obtain accurate results. Based on the results of system testing that has been carried out, it was found that of the 12 cases tested using the expert system, there was 1 case that should have had autism. However, the system diagnosed it as harmful, and 1 case should not have had autism, but the system diagnosed autism. So, it can be concluded that the system's accuracy rate for diagnosing autism is 83%